The well-tempered cosmological constant - Linder, Eric V.; Appleby, Stephen; Appleby, Stephen (IOP Publishing / SISSA, 2018)
Within cubic Horndeski gravity we construct ‘well-tempered’ models where scalar self-tuning cancels any cosmological constant while preserving radiation/matter eras and enabling de Sitter expansion with H independent of Λ, avoiding the usual suppression of all sources.
Keywords: scalar-tensor gravity; self tuning; cosmological constant problem; Horndeski theory; modified gravity; modified gravity